Splendori e rovina del desiderio - Rella, Franco (Scenari, 2021)
Albert Camus wrote in 1950 that Melville to 35 years agreed the annihilation. Camus is certainly referring to the figure of Bartleby in Melville’s story, and perhaps the echo of the mythical Kojève’s seminars on Hegel’s Phenomenology of Spirit, that started emphasizing the theme of desire and his annihilation at the end of the history that is, for Kojève, also the end of man. In the last decades of the last century Bartleby and Kojève emerge as sharp edges in French philosophy, often repeating the Beckett moves, the (here unnamed) author of The Unnamable and Waiting for Godot, who staged the conclusions of Kojève lessons and also the “philosophie du neutre” of Maurice Blanchot.